Density Functional Based Tight Binding Study on Wurtzite ZnO Prismatic Nanoparticles - Minh, Nguyen Viet; Tuoc, Vu Ngoc; Lien, Le Thi Hong (Communications in Physics, 2011)
We have performed the Density Functional Tight Binding (DFTB) study on the structural properties of Zinc Oxide Nanoparticles (NP), focusing on the effects induced by the surfaces and quantum size effect. Effects of surface relaxation and surface stress which is absent in atomistic model are taken carefully into account. The studying Nanoparticle size range up to 2.3nm. We illustrated the structural properties changes by decreasing NP sizes while the typical length of surface relaxation (about 1nm) remain unchanged and comparable with the particle size. The NP electronic properties, i.e. Density of State (DOS), charge transfer in hetero-bond also showed the deviation from bulk material value.